ANALISIS KECERDASAN EMOSIONAL SISWA KELAS IV SD NEGERI 02 SUNGAI AYAK TAHUN PELAJARAN 2022/2023 - Veronika Veronika; Thomas Joni Verawanto Aristo; Yasinta Lisa; Imanuel Sairo Awang; Warkintin Warkintin (STKIP Persada Khatulistiwa Sintang, 2023)
This research is motivated by students who have not been able to recognize their emotions, manage them, motivate themselves, recognize friends' emotions, and build relationships with them at the right time. This study aimed to describe emotional intelligence in grade IV students of SD Negeri 02 Sungai Ayak's academic year of 2022/2023. This form of research is mixed methods. The subjects of this study were grade IV students totaling 32 students, and class teachers. The data collection tools used in this study were questionnaires, observations, interviews, and documentation. Based on the research obtained: 1) The average emotional intelligence of students in the learning process is 78% of students in the category of quite good. 2) Students' average emotional intelligence characteristics 72% of students with fairly good emotional intelligence characteristics. 3) The emotional intelligence of students influences that is, the supporting factor is environmental factors, while the inhibiting factor is the lack of motivational ability oneself. The emotional intelligence possessed by students varies. This is shown by uncontrolled anger, such as fighting, indifference, and being active but less adaptable to the environment. This research shows that the emotional intelligence of grade IV students of SD Negeri 02 Sungai Ayak is still quite good.